(untitled) (Filološke pripombe, 2020)
Exile related trauma emerges from the feeling of loss, which is one of the main topics in Edward Said’s Reflections on Exile. Sigmund Freud, in his work Mourning and Melancholia, states that the loss of the homeland is one of the cardinal reasons for mourning. This has led many exile theorists to analyze works themed around moving or relocating to another place based on the psychology of loss. Presenting the opposing positions of Edward Said, Paul Tabori and John Neubauer on exile literature, as well as their definitions of exile, refuges, expatriats, apatrides, this text focuses on the specific importance of cultural memory in exile literature, which refers to those who don’t live in the country in which they were born, or is authored by them. Implementing Azade Seyhan’s examinations of remembrance and what she refers to as “writing outside the nation”, this paper analyses exile literature as intentional remembrance caused by the feeling of loss, which relies on the restorative ability of cultural memory and aims to connect the past and present in integrative wholeness.